1984
DOI: 10.1161/01.hyp.6.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Direct action of aldosterone on transmembrane 22Na efflux from arterial smooth muscle. Rapid and delayed effects.

Abstract: SUMMARY Acute subcutaneous (s.c.) administration of aldosterone increases ex vivo "Na efflux from rat tail artery smooth muscle, which appears to be due to a specific action on mineralocorticoid receptors. Indeed, this effect is blocked by the antimineralocorticoid compounds RU 28318 [17/3-hydroxy-3-oxo,7 a-propyl(17 a)-pregn 4-ene, 21 potassium carboxylate] and spironolactone. The specific glucocorticoid receptor agonist RU 26988 [ll/3,17/3-dihydroxy-17-(l-propynyl) androesta-1,4,6 trien-3-one] does not modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…This confirmed earlier work by these investigators showing a rapid increase in passive sodium efflux that was insensitive to actinomycin D in intact rat tail artery. 32 These data suggest that aldosterone has a membrane effect that is not mediated by Na + ,K + -ATPase. In our previous study 15 acute administration of aldosterone (15 minutes) caused a depression in carotid sinus baroreceptor function.…”
Section: Discussionmentioning
confidence: 86%
“…This confirmed earlier work by these investigators showing a rapid increase in passive sodium efflux that was insensitive to actinomycin D in intact rat tail artery. 32 These data suggest that aldosterone has a membrane effect that is not mediated by Na + ,K + -ATPase. In our previous study 15 acute administration of aldosterone (15 minutes) caused a depression in carotid sinus baroreceptor function.…”
Section: Discussionmentioning
confidence: 86%
“…Discrepancies in reports may result from indirect effects of other transporters on Na + -K + -ATPase pump activity or from different isoforms expressed in different models and tissues (Summa et al 2004). Again just like for ENaC, Na + -K + -ATPase response to aldosterone seems to involve trafficking of preexisting subunits to the membrane as well as de novo synthesis (El Mernissi & Doucet 1984, BlotChabaud et al 1990, Kolla & Litwack 2000, Summa et al 2001, Musch et al 2008. SGK, an MR target gene, and aldosterone were shown to stimulate long-term effects synergistically but independently (Alvarez de la Rosa et al 2006).…”
Section: Nongenomic Aldosterone Effects In the Kidneymentioning
confidence: 99%
“…Although the effect is persistent and lasting over several days, the involvement of the EGFR signaling pathways indicates a possible nongenomic mechanism (Krug et al 2003, Drumm et al 2006. Furthermore, it has been demonstrated that NHE3 expression is increased via SGK1 and genomic effects on the long-term (Musch et al 2008). Conversely, aldosterone inhibited maximal velocity of NHE3 via ERK1/2 in MTAL, thus reducing bicarbonate reabsorption (Good et al 2006, Watts et al 2006.…”
Section: :1mentioning
confidence: 99%
“…Initially, the classic cytosolic MR protein was suggested to be involved in mediating both nongenomic and genomic aldosterone signaling 2,8 ; however, some studies reported that these nongenomic effects could not be blocked by MR antagonists such as spironolactone. In addition, although rapid, nongenomic effects were elicited by the mineralocorticoids aldosterone, deoxycorticosterone, and 9␣-fludrocortisone, these rapid effects could not be elicited by the glucocorticoids cortisol and corticosterone.…”
Section: Evidence For a Nonclassic Aldosterone Receptor In The Plasmamentioning
confidence: 99%